Clio in the clinic : history in medical practice - Duffin, Jacalyn (University of Toronto Press, 2005)
Clio in the Clinic shows how knowledge of history can shape a physician's view of the profession and how it can be a surprising asset at the bedside for diagnosis and treatment.